IQGAP3 Overexpression Correlates With Poor Prognosis and Radiation Therapy Resistance in Breast Cancer - Hua, Xin; Long, Zhi-Qing; Guo, Ling; Wen, Wen; Huang, Xin; Zhang, Wen-Wen; Lin, Huan-Xin (Frontiers in Pharmacology, 2021)
Background: IQ motif-containing GTPase activating protein 3 (IQGAP3), the latest identified member of the IQGAP family, may act as a crucial factor in cancer development and progression; however, its clinical value in breast cancer remains unestablished. We explored the correlation between IQGAP3 expression profile and the clinicopathological features in breast cancer. Methods: IQGAP3 mRNA and protein levels were detected in breast cancer cell lines and tumor tissues by real-time PCR and western blotting and compared to the normal control groups. Protein expression of IQGAP3 was also evaluated immunohistochemically in archived paraffin-embedded specimens from 257 breast cancer patients, and the associations between IQGAP3 expression level, clinical characteristics, and prognosis were analyzed. We assessed the relationship between IQGAP3 expression and sensitivity to radiation therapy which was determined by subgroup analysis. Results: IQGAP3 was significantly upregulated in breast cancer cell lines and human tumor tissues at both the mRNA and protein level compared to controls. Additionally, high levels of IQGAP3 expression were detected in 110/257 (42.8%) of archived paraffin-embedded breast cancer specimens. High IQGAP3 expression level was significantly related to clinical stage (p = 0.001), T category (p = 0.002), N category (p = 0.001), locoregional recurrence (p = 0.002), distant metastasis (p = 0.001), and vital status (p = 0.001). Univariate and multivariate statistical analysis showed that IQGAP3 expression was an independent prognostic factor among all 257 breast cancer patients in our cohort (p = 0.003, p = 0.001). Subgroup analysis revealed IQGAP3 expression correlated with radioresistance and was also an independent predictor of radiotherapy outcome. Conclusion: Our findings suggest that high IQGAP3 expression predicts poor prognosis and radioresistance in breast cancer. Therefore, IQGAP3 may be a reliable prognostic biomarker in breast cancer and could be used to identify patients who may benefit from radiotherapy.